Audias fabulas veteres : Anatolian studies in honor of Jana Součková-Siegelová - Velhartická, Šárka.; Siegelová, Jana. (Culture and History of the Ancient Near East, 2016)
The publication Audias fabulas veteres. Anatolian Studies in Honor of Jana Součková-Siegelová contains 31 contributions on current research topics in the fields of Ancient Anatolian and Near Eastern Languages, History, Religion, and Literature. The topics cover not only the main languages of this geographical area, such as Hittite, Luwian, Hattian, Hurrian, Akkadian, and Sumerian but also comparative linguistics and the latest methods of digitalising cuneiform texts, as well as religion, mythology and divinities, rituals, proverbs and analysis of geographical and historical documentation. Finally, it offers new analyses of some of the most remarkable texts and text passages of the ancient Anatolian literary tradition.